Superficial digital flexor tendon luxation in a golden retriever - Mitsuhhiro Isaka; Taichi Okayama; Minori Yamaguchi; Wataru Konno (Open Veterinary Journal, 2022)
Background: Luxation of the superficial digital flexor (SDF) tendon involves the dislocation of the tendon from the groove of the calcaneal tuberosity. Although it is common in Shetland sheepdogs and collies presenting with acute, severe, and non-weight-bearing lameness, it is a rare orthopedic disease in golden retrievers. Case Description: A 13- month-old neutered male golden retriever (32.2 kg) with acute right hind lameness and pain, was diagnosed with SDF luxation based on physiological, radiographic, and ultrasound examinations. The surgical procedure used was capsulorrhaphy of the tarsal joint and fixation with Kirschner wire. Postoperatively, the tarsal joint was stretched and externally fixed to prevent tension. The patient showed good gait without pain after pin removal on postoperative day 88. Conclusion: In clinical practice, the possibility of this condition should be considered in golden retrievers presenting with lameness. [Open Vet J 2022; 12(6.000): 851-854]